Effect of time to relapse on overall survival in patients with mantle cell lymphoma following autologous haematopoietic cell transplantation. (28th September 2021) - Riedell, Peter A.; Hamadani, Mehdi; Ahn, Kwang W.; Litovich, Carlos; Brunstein, Claudio G.; Cashen, Amanda F.; Cohen, Jonathon B.; Epperla, Narendranath; Hill, Brian T.; Im, Annie; Inwards, David J.; Lister, John; et al.
Summary: In young and fit patients with mantle cell lymphoma (MCL), intensive induction therapy followed by a consolidative autologous haematopoietic cell transplant (autoHCT) is the standard of care in the front‐line setting. Recently, time‐to‐event analysis has emerged as an important risk assessment tool in lymphoma, though its impact in MCL is not well defined. We utilized the Center for International Blood and Marrow Transplant Research database to evaluate the effect of post‐autoHCT time to relapse on overall survival (OS) over time in 461 patients who underwent autoHCT within 12 months of MCL diagnosis. On multivariate analysis, the impact of relapse on OS was greatest at the six‐month [hazard ratio (HR) = 7·68], 12‐month (HR = 6·68), and 18‐month (HR = 5·81) landmark timepoints. Using a dynamic landmark model we demonstrate that adjusted OS at five years following each landmark timepoint improved with time for relapsing and non‐relapsing patients. Furthermore, early relapse (<18 months) following autoHCT defines a high‐risk group with inferior post‐relapse OS. This retrospective analysis highlights the impact of time to relapse on OS in MCL patients undergoing up‐front autoHCT and emphasizes the need to consider novel therapeutic approaches for patients suffering early relapse.